Contrast sensitivity measured by two different test methods in healthy, young adults with normal visual acuity - Koefoed, Vilhelm F.; Baste, Valborg; Roumes, Corinne; Høvding, Gunnar (Acta ophthalmologica (Oxford, England), 2015)
Purpose This study reports contrast sensitivity (CS) reference values obtained by two different test methods in a strictly selected population of healthy, young adults with normal uncorrected visual acuity. Based on these results, the index of contrast sensitivity (ICS) is calculated, aiming to establish ICS reference values for this population and to evaluate the possible usefulness of ICS as a tool to compare the degree of agreement between different CS test methods. Methods Military recruits with best eye uncorrected visual acuity 0.00 LogMAR or better, normal colour vision and age 18–25 years were included in a study to record contrast sensitivity using Optec 6500 (FACT) at spatial frequencies of 1.5, 3, 6, 12 and 18 cpd in photopic and mesopic light and CSV‐1000E at spatial frequencies of 3, 6, 12 and 18 cpd in photopic light. Index of contrast sensitivity was calculated based on data from the three tests, and the Bland–Altman technique was used to analyse the agreement between ICS obtained by the different test methods. Results A total of 180 recruits were included. Contrast sensitivity frequency data for all tests were highly skewed with a marked ceiling effect for the photopic tests. The median ICS for Optec 6500 at 85 cd/m2 was −0.15 (95% percentile 0.45), compared with −0.00 (95% percentile 1.62) for Optec at 3 cd/m2 and 0.30 (95% percentile 1.20) FOR CSV‐1000E. The mean difference between ICSFACT85 and ICSCSV was −0.43 (95% CI −0.56 to −0.30, p < 0.00) with limits of agreement (LoA) within −2.10 and 1.22. The regression line on the difference of average was near to zero (R2 = 0.03). Conclusion The results provide reference CS and ICS values in a young, adult population with normal visual acuity. The agreement between the photopic tests indicated that they may be used interchangeably. There was little agreement between the mesopic and photopic tests. The mesopic test seemed best suited to differentiate between candidates and may therefore possibly be useful for medical selection purposes.